2017
DOI: 10.5588/ijtld.16.0775
|View full text |Cite
|
Sign up to set email alerts
|

Implementing isoniazid preventive therapy in a tuberculosis treatment-experienced cohort on ART

Abstract: SETTING Urban clinical research site in Durban, South Africa OBJECTIVE To describe the outcomes associated with implementation of isoniazid preventive therapy (IPT) in a cohort of TB treatment experienced HIV infected patients on antiretroviral therapy (ART). DESIGN We conducted a secondary analysis of data collected between October 2009 and October 2013 from patients enrolled in a prospective cohort study conducted in Durban, South Africa. RESULTS There were 402 patients enrolled in the parent study. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…[ 9 20 21 ] Earlier, a qualitative study in Ethiopia concluded that integration of health system services was important factor to improve adherence and IPT completion rate[ 22 ] A prospective study in South Africa evaluating cohort of TB treatment-experienced HIV-infected patients in ART visits found a higher IPT completion rate of 86.8% when IPT visits were successfully integrated with existing ART visits. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 20 21 ] Earlier, a qualitative study in Ethiopia concluded that integration of health system services was important factor to improve adherence and IPT completion rate[ 22 ] A prospective study in South Africa evaluating cohort of TB treatment-experienced HIV-infected patients in ART visits found a higher IPT completion rate of 86.8% when IPT visits were successfully integrated with existing ART visits. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…The first was the TB Recurrence upon Treatment with HAART (TRuTH) CAPRISA 005 study (Maharaj et al, 2017; Sivro et al, 2017). This prospective cohort study, conducted between 2009 and 2013, aimed to assess risk factors associated with progression to recurrent TB disease during a 3-year longitudinal follow up in HIV-infected persons who began ART during treatment of the previous TB episode.…”
Section: Methodsmentioning
confidence: 99%
“…This opened the possibility to evaluate the COR signature in rare longitudinal cohorts from whom only biobanked PBMCs are available. In this study we aimed to determine the prognostic value of this 11-gene COR signature for recurrent TB in people living with HIV who participated in the “TB Recurrence upon Treatment with HAART” (TRuTH) study conducted at the Centre for the Aids Programme of Research In South Africa (CAPRISA) in Durban, South Africa (Maharaj et al, 2017; Sivro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study included 402 patients from whom 344 patients were authorized to receive IPT, and 212 initiated IPT therapy. The implementation of IPT among patients with ART and TB was well tolerated, with a good percentage of completion and a smaller number of TB cases diagnosed after performing IPT [20].…”
Section: Resultsmentioning
confidence: 97%